PERUBAHAN BUDAYA TINGGI BERITA INVESTIGASI MENJADI BUDAYA POPULER - Roswita Oktavianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2018)
The characteristics of mass media as a source of information constanly changes according to the dynamics of regulation and the development of the media industry. This change has an impact not only on entertainment programs but also on news broadcast programs. As high culture content, investigative news programs should be produced through a number of investigative stages with content and quality that is dif erent from regular news. In reality, media workers are required to work instantly according to the logic of the media industry. Investigative news has shifted from formerly being high culture to popular culture. With qualitative approach and case study method, this study aims to find out how media workers changed investigative news from high culture into popular culture. The primary data collection method in the form of interview was conducted with an informant, a media worker in one of many private television investigative programs. The study found that the culture industry on investigative news was applied not only on the content but also the human resources behind it. Investigative news is produced by journalists who mostly have no investigative competence. Investigative news is based on the quantity of news produced, quick production, budget ef iciency, market tastes, and the interests of owners and advertisers. Transformation of high culture investigative news programs to popular culture ultimately impacted the quality of investigative newsKarakteristik media massa sebagai sumber informasi terus berubah mengikuti dinamika regulasi dan perkembangan industri media. Perubahan ini berdampak tidak hanya pada program hiburan tetapi juga program siaran berita. Sebagai konten dengan budaya tinggi (high culture), program berita investigasi seharusnya diproduksi melalui sejumlah tahapan investigatif dengan konten dan kualitas yang berbeda dengan berita reguler. Pada kenyataannya, pekerja media dituntut bekerja secara instan mengikuti logika industri media. Berita investigasi berubah dari semula memiliki budaya tinggi menjadi budaya populer (popular culture). Dengan pendekatan kualitatif dan metode studi kasus maka penelitian ini bertujuan mengetahui bagaimana pekerja media menciptakan berita investigasi dari budaya tinggi menjadi budaya populer. Teknik pengumpulan data primer berupa wawancara dilakukan kepada informan, pekerja media di salah satu program investigatif televisi swasta. Penelitian menemukan bahwa industri budaya pada berita investigasi dilakukan pada tidak hanya pada konten tetapi juga sumber daya manusia di dalamnya. Berita investigasi diproduksi oleh jurnalis yang sebagian besar tanpa kompetensi investigasi. Berita investigasi berpatokan pada besarnya kuantitas berita yang dihasilkan, durasi produksi yang singkat, efisiensi anggaran, selera pasar, serta kepentingan pemilik dan pengiklan. Perubahan program berita investigasi dari budaya tinggi ke budaya populer ini pada akhirnya berdampak pada kualitas berita investigasi.